MENTAL HEALTH CONCERNS IN RELATION TO BULLYING, FEELINGS AND FRIENDSHIP, EMOTIONAL DISTURBANCES IN HOME AND SCHOOL, AMONG ADOLESCENTS SEEN IN THE PAEDIATRIC OBESITY AND DIABETES CLINIC - Ali, Hakima Muhamad; Affendi, Balqis Nur Sabrina; Zanalabidin, Nur Aimi Nabilah; Zaini, Azriyanti Anuar (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION The issues surrounding childhood obesity and chronic illnesses such as diabetes, in relation to their physical appearance, and mental well-being are always a concern. This study explores potential insights into the experiences of adolescents with obesity and diabetes and their implications towards physical and mental health. METHODOLOGY Patients aged 12 to 18 years old attending the obesity and diabetes clinic at UMMC were invited to participate in the study. A questionnaire-based assessment was offered. The questionnaire was adapted with consent from the NHMS 2017 committee. The study was approved by UMMC ethics committee. We analysed 4 components which includes bullying, feelings and friendship, home and school experiences, as well as emotional disturbances. A scoring system was adapted to stratify risks. RESULT A total of 43 patients responded to the questionnaire. Forty-four percent (n=19) were males with 7.0% (n=3) recruited from the obesity clinic and 93.0% (n=40) from the diabetes clinic. Their mean age was 14.8 years old. The responses were grouped according to either high risk or low risk depending on the scores. None reported bullying. One in four (n=10) scored high risk when questioned about their feelings (which includes suicidal ideation) and friendship. Thirteen (30.2%) scored high risk for experiences at home and school (which explores school absences and parental support). Three (7%) expressed high-risk score for emotional component which includes anxiety, agitation, motivation, and self-worth. CONCLUSION Childhood obesity and chronic illness like diabetes confer a higher risk for psychological disturbances. Addressing their risks and mental health concerns should be prioritised to prevent further deterioration. These study findings highlight the issues and suggest that further liaison with other medical professionals e.g., child psychologistst, is warranted.